C4 Pictet–Spengler Reactions for the Synthesis of Core Structures in Hyrtiazepine Alkaloids - Abe, Takumi; Haruyama, Tomohiro; Yamada, Koji (Synthesis, 2017)
The hyrtiazepine alkaloids are a family of bisindole natural products that have the azepinoindole backbone. We developed a biomimetic approach by constructing the azepinoindole core in a one-pot manner through 1,4-diazabicyclo[2.2.2]octane/2,2,2-trifluoroethanol (DABCO/TFE) promoted Pictet–Spengler reaction onto the C-4 position of tryptophan. This strategy allowed the synthesis of common key structures of these families. The key intermediate can be converted into the 3H-pyrano[2,3-b:5,6-e′]diindol intermediate present in hyrtimomines A and B, as well as the azepinoindole core present in fargesine.
Keywords: Pictet–Spengler reaction; indole alkaloids; azepinoindoles; biomimetic synthesis; cyclizations; stereoselectivities